(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Consumer food safety concerns storage facilities, family practices around meals and leftovers and planning capabilities influence the quantity of food waste created in the household. In this study a survey was conducted to determine how attitudes towards packaging might influence motivations to reduce food waste and to explore reasons for household food waste through the distribution of a structured questionnaire to households. According to this survey it has been shown that about 35% of consumers say that packaging of a product influence their purchase. Although consumers awareness is an important factor to reduce food waste.